Electric Distribution Network Planning (Power Systems,, 2018)
This book highlights the latest research advances in the planning and management of electric distribution networks. It addresses various aspects of distribution network management including planning, operation, customer engagement, and technology accommodation. Given the importance of electric distribution networks in power delivery systems, effectively planning and managing them are vital to satisfying technical, economic, and customer requirements. A new planning and management philosophy, techniques, and methods are essential to handling uncertainties associated with the integration of renewable-based distributed generation, demand forecast, and customer needs. This book covers topics on managing the capacity of distribution networks, while also addressing the future needs of electric systems. The efficient and economical operation of distribution networks is an essential aspect of ensuring the effective use of resources. Accordingly, this book addresses operation and control approaches and techniques suitable for future distribution networks.